A brief history of poultry nutrition over the last hundred years. Issue 4 (21st October 2016) - ELWINGER, K.; FISHER, C.; JEROCH, H.; SAUVEUR, B.; TILLER, H.; WHITEHEAD, C.C.
Abstract : The science and practice of poultry nutrition has changed greatly over the last hundred years, moving from a backyard enterprise to the modern computer-controlled production of whole diets formulated to specific nutrient compositions. This has become possible as a result of the identification of individual nutrients and their metabolic roles. Although the word 'protein' was first used in 1834, it was not until the 1950s that the avalanche of research on protein and amino acid requirements of poultry started. Energy content of feeds did not become a consideration until the 1940s when the concept of metabolisable energy was introduced. The term 'vitamin' was first proposed in 1912 to describe the essentiality of thiamine. The term was later extended to cover other essential compounds needed in small quantities. By the 1940s all the remaining 12 vitamins had been identified, and in the 1970s the importance of the vitamin D metabolites was discovered. The importance of calcium and phosphorus for both growing and laying birds was identified in the early stages of poultry keeping and requirements and dietary ratios were established. More recently, the introduction of feed phytase has allowed lowering of both phosphorus and calcium concentrations. Carbohydrase enzymes have also been development for addition to feeds. The importance of sodium, phosphorus and chloride in maintaining electrolyte balance was identified. Trace minerals were usually supplemented in diets as inorganic salts but organic chelates or proteinates have been found in recent years to be absorbed more efficiently. Antibiotics were widely used as growth promoters but their banning, especially in Europe, has led to the search for alternative additives with growth or health benefits. Poultry nutrition is now a scientifically mature subject but changes in industrial practice can be expected to continue, though probably at a slower pace than in recent years.